Motor skills proficiency and body composition among 8 to 10 year-old children / Noor Azila Azreen Md Radzi - Md Radzi, Noor Azila Azreen (2013)
There is a prevalence of overweight and obesity issues among children worldwide today. A lack of physical activities been seen as the main factor that contributes to the dramatically increase of the overweight and obesity problems. Although reseachers have found that children who are overweight and obese are generally less active, the exact relationship between motor skills proficiency and obesity is still limited. The purpose of this study were to compare the motor skills proficiency between underweight, normal, overweight and obese children and to determine the relationship between motor skills proficiency and body composition among 8 to 10 years old children. This study involved 112 children aged between 8 to 10 years old (56 boys, 56 girls). Their motor skills proficiency was assessed using Bruininks-Oseretsky Test Second Edition- Short Form. Meanwhile, their body composition was determined by the skindfold thickness measurement. The result showed that there was a significant differences between underweight, normal, overweight and obese children in motor skills proficiency (p < 0.05). It was also reported that there was a significant correlation between motor skills proficency and body comporsiton (r = - 0.80). This study concludes that motor skills proficency is inversely correlated with body composition. The most superior group in motor skill is the normal weight children followed by underweight, overweight and obese children.